(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2012)
Septicemia is a common cause of morbidity and mortality among children in developing world. Clinicians are in need of better diagnostic markers to diagnose septicemia. This study was carried out to evaluate the usefulness of interleukin-6 (IL-6) as a marker for the diagnosis of septicemia in children. Blood samples from 202 clinically suspected cases of septicemia and 20 age and sex matched healthy children were studied. On the basis of clinical features, blood cultures and C-reactive protein (CRP) analysis results, study populations were categorized as culture proven septicemia 35(15.77%), probable septicemia 125(56.31%), non-septicemic febrile patient 42(18.92%) and healthy control 20(9.0%). Out of 35 culture positive cases, IL-6 estimation was done in 32 samples. In culture proven septicemia group, 28 (87.5%) had IL-6 levels above cut-of value (>137 pg/ml). In 20 probable septicemia and 10 non-septicemic febrile group, IL-6 level above cut-off value were found in 06 (30%) and 01(10%) cases respectively. None of the healthy control group showed the concentration of IL-6 above cut-off value. The sensitivity and specificity of IL-6 were 65.38% and 95% respectively. Measurement of IL-6 may be a good marker to diagnose septicemia in children but this needs further evaluation on larger population. JCMCTA 2012; 23(1): 21-25